Event Management PT Neo Expo Promosindo Dalam Membangun Citra Perusahaan (Studi Deskriptif Pada Event IFBC 2022) - Meilina, Indah; Patrianti, Tria (Educationist: Journal of Educational and Cultural Studies, 2023)
Business competition in the scope of service providers such as Event Organizers (EO) in the current era is very strong. Every company competes to offer various kinds of advantages. In facing this competition, PT Neo Expo Promotionndo held roadshow events to several cities in collaboration with UMKM through the IFBC 2022 exhibition. The aim of this research is to find out how event management is carried out by PT. Neo Expo Promotionndo in building the company's image. The theory used in this research is event management theory from Joe Goldblatt, namely Research, Design, Planning, Coordination and Evaluation. Nimpoeno's Image Formation Theory, namely Perception, Cognition, Motivation and Attitude. This research use desciptive qualitative approach. Data collection techniques include in-depth interviews and documentation. The results of this research began with research by conducting random interviews with a number of franchise business actors. Design, using two strategies, above the line and below the line. Planning, creating an event timeline. Coordination, coordinating events. Evaluation, the results are quite satisfying that the IFBC 2022 event has had a positive impact on the cast participants. The formation of Nimpoeno's image, namely Perception, Cognition, Motivation and Attitude at the IFBC 2022 event, resulted in visitors feeling satisfied with the series of activities that provided education about franchises, which in the end they were interested in buying franchises, and had a positive impact on the participants because of the transactions that occurred and comprehensive series of activities. The conclusion from this research is that good event management can build a company's image.